Disease-modifying therapies and hematological disorders: a systematic review of case reports and case series - Scavone, Cristina; Liguori, Valerio; Adungba, Olusola Jephthah; Cesare, Daniele Di Giulio; Sullo, Maria Giuseppa; Andreone, Vincenzo; Sportiello, Liberata; Maniscalco, Giorgia Teresa; Capuano, Annalisa (Frontiers in Neurology, 2024)
Introduction Disease modifying therapies (DMTs) used to treat multiple sclerosis (MS) can be associated to the occurrence of hematological disorders. This systematic review aims to provide an overview of these events occurring in real-life conditions, by describing case reports and series published in the literature. Methods A literature search of all publications up to January 5th 2024 on the Medline and Embase databases was carried out. The results were presented both in the text and in tables. Results Sixty-seven case reports/series were included in this review, of which more than half related to alemtuzumab, natalizumab and ocrelizumab. The publication date of included studies ranged from 2006 to 2024. The majority of case reports and series described the occurrence of late-onset hematological disorders (events that occurred more than 30 days after the first DMT administration), mainly represented by case of neutropenia, autoimmune hemolytic anemia and immune thrombocytopenia. All cases reported a favorable outcome, apart one case report that described a fatal case. Among included cases, 4 articles, all related to natalizumab, described the occurrence of myeloid disorders in 13 newborns from mother receiving the DMT. Discussion Considering the limitations identified in the majority of included studies, further ad hoc studies are strongly needed to better evaluate the hematological disorders of DMTs. Meantime, the strict monitoring of treated patients for the occurrence of these toxicities should be highly recommended.